The Effect of Taxpayers' Suspicion Toward Existing Tax Laws on Tax Audit Effectiveness - Fariz Rizky Hidayat (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2025)
The purpose of this study is to examine how taxpayer distrust of current tax laws affects the efficiency of tax audits. Tax audits are a means of communication between tax authorities and taxpayers in addition to being an instrument to confirm tax compliance. The audit process can be affected by resistance and uncooperative behavior caused by a cynical attitude towards tax law. To investigate the evolution of research related to tax audits, this study used bibliometric analysis on 433 journal articles published between 2021 and 2025 using Publish or Perish and VOSviewer tools. Seven clusters with a wide range of subjects were revealed by this study, indicating that the field of tax audit has received substantial attention and development. To directly investigate the psychological impact of suspicion on audit smoothness, more qualitative research is needed.